Pengaruh Brand Image Dan Brand Awareness Terhadap Keputusan Pembelian Produk Tehbotol Sosro Di Kota Cimahi - Rini Handayani; Tiara Kamilla (STIKes Ibnu Sina Ajibarang, 2023)
This research was conducted on Tehbotol Sosro consumers in the city of Cimahi. The purpose of this study is to determine how much the influence of brand image and brand awareness on purchasing decisions both partially and simultaneously. The research methods to be used in this study are discriptive and associative methods. In this study, the unit of analysis is individuals, namely consumers of Tehbotol Sosro in the city of Cimahi. The sample in this study was 97 respondents. Sampling with certain considerations or criteria is a sampling technique used in this study. The analysis method uses multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study shows that there is an influence both partially and simultaneously on exogenous variables (brand image and brand awareness) on endogenous variables (purchase decisions).